Adding physical activity to intensive trauma-focused treatment for post-traumatic stress disorder: results of a randomized controlled trial - Voorendonk, Eline M.; Sanches, Sarita A.; Tollenaar, Marieke S.; Hoogendoorn, Elisabeth A.; de Jongh, Ad; van Minnen, Agnes (Frontiers in Psychology, 2023)
Introduction: This randomized controlled trial examined whether intensive trauma-focused treatment (TFT) for post-traumatic stress disorder (PTSD) could be augmented by physical activity. Methods: A total of 119 patients with PTSD were randomly assigned to a physical activity condition (PA; n = 59) or a non-physical activity control condition (nPA; n = 60). The 8-day intensive TFT programme consisted of daily prolonged exposure, EMDR therapy, and psychoeducation, which was complemented with physical activities versus controlled mixtures of guided (creative) tasks. As a primary outcome, the change in clinician and self-reported PTSD symptoms from pre- to post-treatment and at 6-month follow-up were measured. Results: Intent-to-treat linear mixed-effects models showed no significant differences between the PA and nPA conditions on change in PTSD severity. Clinician and self-reported PTSD symptoms significantly decreased for both conditions, with large effect sizes (e.g., CAPS-5 dpre-post = 2.28). At post-treatment, 80.0% in the PA, and 82.7% in the nPA condition no longer met the diagnostic criteria for PTSD. Regarding loss of Complex PTSD this was 92.5% and 95.0%, respectively. Conclusions: With either adding physical or non-physical activities, intensive TFT is very effective for the treatment of (Complex) PTSD, as reflected by large effect sizes and loss of diagnostic status in both groups. Trial registration: trialregister.nl Identifier: Trial NL9120.